Oral Arts in the Riffian Amazigh Community: An Analysis of the Importance and Functions of Folk Riddles - El Azzouzi, Monaim (Africana Studia, 2024)
The present paper aims at highlighting the importance and main functions of folk riddles in the Riffian Amazigh community. It demonstrates that riddles, as the case with other folk arts such as folk tales, poetry, etc., constitute a self-contained literary genre that played and still play considerable roles in people’s lives. By making use of a corpus of a significant number of riddles, this paper seeks to objectively and accurately account for the importance and functions that characterise such Riffian Amazigh riddles. The data has been collected based on a fieldwork method that relied both on observation and on interviews. On the basis of the collected data, the present paper analyses the didactic benefits of these riddles and their contributions to developing cognitive skills and critical reasoning. Most importantly, it highlights the riddles’ roles in imparting cultural norms and patterns as they preserve many Riffian Amazigh language and cultural patterns that have either disappeared or are disappear ing nowadays. Keywords: Riddles, Ethnofraphy, Amazigh, Riff.